Asuhan Keperawatan Pada Ny.Y Dengan Gangguan Reproduksi: Myoma Uteri Diruang Dahlia RSUD Pandan Arang Boyolali - Lestari, Tri; , Sulastri, S.Kp., M.Kes (2015)
Background : Myoma uterine are benign tumors of the uterine muscle, based on the location and magnitude can provide clinical symptoms such as bleedin. Myoma uteri or commonly referred to as fibfimioma uterus, uterine leiomyomas, or uterine fibroids are benign neoplasms derived from smooth muscle wall of the uterus is found in 20-25 % of women over the age of 35 years. The danger of myoma uteri in case of bleeding and not treated immediately will cause anemia and during reproduction can lead to infertility. Objective: To determine nursing care in patients with myoma uteri reproductive disorders that include assessment, intervention, implementation and evaluation of nursing. Results: After 3x24 hour nursing care for patients showed bleeding can be treated, the patient's pain scale was reduced from 7 to 3 scale, improved nutritional status of patients and patients already know about myoma uteri. Conclusion: Cooperation between the health care team, patients and families are very necessary for the success of nursing care to patients. Keywords: Myoma uterine, Bleeding, Nursing Care.